Pengaturan Hukum terhadap Periklanan dan Informasi Kesehatan dalam Medical Tourism Indonesia - Lala Anggraita Permata Aji (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The medical tourism industry in Indonesia has great potential for economic growth and development of health services. However, to ensure international patients receive accurate information and quality care, proper legal regulation of health information and advertising is essential. This article presents an analysis of the legal arrangements related to advertising and health information in Indonesian medical tourism. Based on a normative juridical approach, this article reviews relevant legal regulations, such as Regulation of the Minister of Health of the Republic of Indonesia Number 76 of 2015 concerning Medical Tourism Services.